THE EFFECT OF SERVICE QUALITY AND INPATIENT FACILITIES ON TBC PATIENT SATISFACTION AT THE RIK UNIT OF DR. SOETOMO GENERAL HOSPITAL IN SURABAYA - Farid Tri Prasetyo (Pedagogic Research-Applied Literacy Journal, 2026)
This study aims to analyze and understand the "Effect of Service Quality and Inpatient Facilities on TB Patient Satisfaction in the RIK Environment of Dr. Soetomo General Hospital, Surabaya." Therefore, the researcher aims to provide readers with accurate data. TB also has a high mortality rate in Indonesia due to its relatively easy transmission, such as through the air, through objects used by TB patients, and so on. Therefore, it requires quite intensive care so that patients can live healthy lives. Therefore, the quality of service in hospitals is very important, and the researcher is very interested in this analysis.